Pope Leo and Chalcedon: how to prepare, appreciate and defend a problematic council - Philippe Blaudeau (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
In the middle of the 5th century, in a context where the Alexandrian and Constantinopolitan models were experiencing an exacerbation of their rivalry, the See of Rome also put its claims to the test of the ecclesial realities of the Eastern Roman Empire. Under Bishop Leo’s leadership, Rome then pretended to exercise a primacy based on the principle of solicitude for all the Churches. Above all, the Pope produced a statement of faith, The Tome to Flavian (June 449), which was supposed to give a perfect defi nition of the (diphysite) faith. Paradoxically, his remoteness and peripheral location with regard to the main decision-making centers of the pars orientis gave him real freedom of speech and a certain capacity for intervention. Therefore, during this particular period of its history, the Apostolic See could express a strong claim to authority. The outbreak of the Christological crisis and its treatment up to the Council of Chalcedon, and the Miaphysite controversy which followed it (448–460) were decisive points of verification for it. In effect, a real distance was observed between the formulation and execution of the Roman discourse, forcing the Pope to adapt his agenda to some extent. Egypt, in fact, was henceforth out of reach of Roman undertakings, while the antiochian East was moving away and Jerusalem, considered unreliable, seemed reduced to a secondary role. On the other hand, Constantinople remained central even though it did not fi nd a place in the order of the Petrine sieges. Faced with this major geo-ecclesiological challenge, Leon had to take account of the forces at work. Initially minority (449–450), his position seemed to be strengthened with the advent of Marcian. However, in spite of appearances, the support given to him by the imperial couple was only partial and conditional. Above all, the contrasting decisions of the Council of 451 forced Leon not to be satisfi ed with half a success. Faced with the persistent disagreement over the 28th canon, the Pope sought to strengthen his strategic position at the interface between power and the imperial Church, in order to facilitate the actualization of his claims in a refractory space, where his confrere Anatolius of Constantinople was pursuing other designs, particularly in the direction of the Illyricum. For a short period (452–457), Leon succeeded in establishing a permanent embassy to Marcian, assumed by Julian, the bishop of Cos. But with the change of emperor (457), this special connection was abolished. This disappearance had serious consequences. It was at the origin of a progressive reduction of infl uence in spite of pontifical attempts to compensate it. Therefore, when anti-Chalcedonian opposition threatened to spread from Alexandria (457–460), the Bishop of Rome had to return to the principle of cooperation with his colleague, the Bishop of Constantinople, to guarantee the integrity of Chalcedonian decisions in matters of faith. This constrained choice was not implemented without embarrassing misunderstandings between the two partners, who were nevertheless condemned to come to an agreement. Thus, from 448 to 460, the Pope's struggle appears intense and full of twists and turns. It is also well documented, in particular thanks to several collections of papal letters (collections Ratisbonensis, Grimanica and Avellana). These exchanges make it possible to study further the ways in which Leon wanted to be informed in order to act with more efficiency. Thus, he gave priority to the information transmitted by his representatives over any other consideration, whether they were sent to a legation or whether a correspondent of Western origin and assimilated to a charg? d'aff aires, Julian of Cos, served his interests. If he was deprived of such sources, the Pope then gave preference to the testimony of the bishops, fi rst and foremost that of Constantinople, to ensure the truth of the facts. But the unequal disposition of his confreres to inform him sometimes obliged him to form his judgment according to the indications transmitted by clerics and monks who called him to the rescue. Sometimes he was even forced to face a problematic lack of news. In such cases, his correspondence shows his concern : he insisted in order to get information from his addressees about a situation that was decidedly difficult to control.